The transitional period redefined as the early Lambayeque period : a study of elite female burials at San José de Moro - Wittholt Leigh, Corissa (2015)
It is a common idea that men in Pre‐Colombian Peru held the socio‐political power.  Recently, many female elite burials from the Moche, Transitional and Lambayeque Periods are changing this idea.  At least in these cultures, there appears to be a continuity of burials of high status women (possibly priestesses) and the matter in which they were treated and interred. Based on this evidence, in this thesis, I explain that based on the recent available archaeological data, that I believe The Transitional Period is in fact The Early Lambayeque period, of which very little data has been excavated.